MASTERING THE CONCEPT OF THE OPTIMAL SIZE OF AN URBAN UNIT UNDER THE NEW VISION OF SUSTAINABLE URBAN DESIGN - DAHMANI, K.; ADAD, M. CH.; MEQUIGNON, M. (Courrier du Savoir, 2017)
The shaping of a design is a thought or existential construction. The first aim is to promote reconciliation of all complex components. The delimitation of an urban system is to realize the conceptualization of loads capacity. It always starts with simple components and organisms, sometimes separated, to become more complex over time. It is possible to compare it with healthy body. Urban units are destined to satisfy optimally the physiographic, biological, sociological, aesthetic, technological, economic, legal and organizational criteria. The paper tents to answer the two following questions. Is the phenomenon of urban sprawl is unlimited? What are the criteria which determine the urban growth threshold in order to achieve better sustainable urban projects?